(x-99) (1/30 + 1/32 + 1/34 - 1/36 - 1/38) = 0
SUy ra x - 99 = 0
VẬy x =99
\(\frac{x-69}{30}+\frac{x-67}{32}+\frac{x-65}{34}=\frac{x-63}{36}+\frac{x-61}{38}\)
\(\Leftrightarrow\frac{x-69}{30}+\frac{x-67}{62}+\frac{x-65}{34}-\frac{x-63}{36}-\frac{x-61}{38}=0\)
\(\Leftrightarrow\frac{x-69-30}{30}+\frac{x-67-32}{32}+\frac{x-65-34}{34}-\frac{x-63-36}{36}+\frac{x-61-38}{38}=0\)
\(\Leftrightarrow\frac{x-99}{30}+\frac{x-99}{32}+\frac{x-99}{34}-\frac{x-99}{36}-\frac{x-99}{38}=0\)
\(\Leftrightarrow\left(x-99\right)\left(\frac{1}{30}+\frac{1}{32}+\frac{1}{34}-\frac{1}{36}-\frac{1}{38}\right)=0\)
Vì \(\frac{1}{30}+\frac{1}{32}+\frac{1}{34}-\frac{1}{36}-\frac{1}{38}\ne0\)
\(\Rightarrow x-99=0\)
\(\Rightarrow x=99\)
\(\frac{x-69}{30}+\frac{x-67}{32}+\frac{x-65}{34}=\frac{x-63}{36}+\frac{x-61}{38}\)
\(< =>\frac{x-69-30}{30}+\frac{x-67-32}{32}+\frac{x-65-34}{34}-\frac{x-63-36}{36}-\frac{x-61-38}{38}=0\)
\(< =>\frac{x-99}{30}+\frac{x-99}{32}+\frac{x-99}{34}-\frac{x-99}{36}-\frac{x-99}{38}=0\)
\(< =>\left(x-99\right).\left(\frac{1}{30}+\frac{1}{32}+\frac{1}{34}-\frac{1}{36}-\frac{1}{38}\right)=0\)
Do \(\frac{1}{30}+\frac{1}{32}+\frac{1}{34}-\frac{1}{36}-\frac{1}{38}\ne0\)
\(< =>x-99=0\)
\(< =>x=99\)